Effects of Traditional and Alternative Routes of Teacher Certification on Student Achievement - Hegwood, Jenita Carroll (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2018)
The demand for accountability over the past decades has altered the landscape of educational success determinants. However, even before the beginning of the advocacy for accountability, various studies were focused on ways of improving test scores. The implementation of the No Child Left Behind Act has forced schools and institutions to look at programs to ensure the success and accountability of students at the elementary and high school level. Supporters of the No Child Left Behind Act believe the emphasis on test results will improve the academic success for all students (White, n.d.). Students are now tested every year to determine their progress from year to year. This helps parents, school leaders, and teachers measure teacher growth and student learning. This new assessment system in schools has resulted in teachers having to pay more attention to the requirements of a test and student achievement. States are now forced to produce effective and highly qualified teachers. One of the most critical factors affecting student achievement is the teacher. An effective teacher helps students outperform those students who are not served by an effective teacher (No Child Left Behind Toolkit for Teachers, 2004).